Lifestyle factors associated with being overweight and obesity in children and adolescents: a cross-sectional study in Zhejiang, China - Pan, Xiaoting; Jiang, Chaoyi; Wang, Wenqing; Lin, Jianfeng (Frontiers in Public Health, 2025)
BackgroundThe prevalence of overweight and obesity among children and adolescents aged 7 to 17 in China is increasingly concerning. Additionally, there is a notable phenomenon where height does not correspond with weight. This study aimed to investigate the prevalence of overweight and obesity in this demographic, explore associations with lifestyle factors, and propose strategies for health promotion.MethodsThis study combines a questionnaire survey with field interviews. Using stratified cluster random sampling, we selected 2,243 primary and middle school students from 49 counties in Zhejiang, China, for the questionnaire survey. Furthermore, we conducted semi-structured interviews with 52 parents.ResultsAmong the 2,243 participants surveyed, 523 were classified as either overweight or obese, resulting in a detection rate of 23.32%. The prevalence of overweight and obesity was higher in boys compared to girls (25.6% vs. 21.1%, p = 0.01). Additionally, the rates among adolescents and children in urban areas were greater than those in rural areas (25.8% vs. 20.5%, p = 0.003). Logistic regression analysis identified several risk factors for overweight and obesity: male gender (OR = 1.846; CI = 1.287 ~ 2.649; p = 0.001), 7 days/week the highest frequency of fried food consumption per week (OR = 88.293; CI = 49.369 ~ 157.905; p < 0.001), 7 days/week the highest frequency of night snacking (OR = 13.24; CI = 7.176 ~ 24.429; p < 0.001), and diets prefer sweetness (OR = 26.299; CI = 15.073 ~ 45.885; p < 0.001), saltiness (OR = 14.672; CI = 8.972 ~ 23.992; p < 0.001), and spiciness (OR = 1.967; CI = 1.125 ~ 3.438; p = 0.018). Conversely, 7 days/week the highest frequency of moderate-to- vigorous physical activities per week was associated with a lower risk of overweight and obesity (OR = 0.137; CI = 0.057 ~ 0.328; p < 0.001). Notably, 84% of parents reported that their children rarely shared interesting stories during school breaks, highlighting the common occurrence of “quiet ten minutes” between classes.ConclusionThe issue of overweight and obesity among children and adolescents in China is significant, particularly among boys in primary schools. An obesogenic environment contributes to this problem, influenced by changes in dietary habits, exercise patterns, and sociocultural factors. Preventing and controlling overweight and obesity among adolescents and children requires the collective efforts from all sectors of society, including government departments, educational institutions, communities and families. Preventative measures should include lifestyle modifications including exercise and dietary adjustments.